Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Scramble Terhadap Keaktifan Belajar Pendidikan Agama Islam Siswa Kelas VII SMPN 5 Bukittinggi - Optalia, Juwita; Aprison, Wedra; Karim, Hamdi Abdul; A, Arifmiboy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the learning process that is still centered on the teacher, this results in low student learning activity. Because it is caused by the lack of variation in learning models used during the teaching and learning process. In this situation, students only listen and pay attention to the teacher's explanation without any feedback, so they feel bored and sleepy during the teaching and learning process. Therefore, the purpose of this study was to determine the significant and positive influence of the Scramble Type Cooperative Learning Model on the learning activity of Islamic Religious Education of class VII students at SMPN 5 Bukittinggi. This study is a quantitative study using the Quasi Experiment method with a nonequievalent control group design. Data collection techniques in this study were observation, learning activity questionnaires, and documentation. The population in this study was 181 students and the research sample was 29, with a sampling technique of random sampling. Decision making is based on the Independent sample t-test, where the data tested were the results of the posttest of the two classes. By using a significance level of 5% or = 0.05, a sig ? of 0.019 was obtained. Because the value of Sig ? <0.05 (0.019 <0.05) then H0 is rejected and Ha is accepted. Thus it can be concluded that there is a significant influence of using the scramble type cooperative learning model on the activeness of learning Islamic religious education of class VII students of SMPN 5 Bukittinggi. So it can be concluded that the large influence of using the scramble type cooperative learning model is 21.4% compared to not using the scramble type cooperative learning model which is 7.1% with an average difference of 12.89.